2001
DOI: 10.21236/ada393566
|View full text |Cite
|
Sign up to set email alerts
|

National Missile Defense - 21st Century Long Wall?

Abstract: The paper puts forth the thesis that the security challenges of the twenty-first century require the addition of National Missile Defense (NMD) to U.S. nuclear deterrence strategy. It discusses this issue with the help of an historical analogy that compares the U.S. decision to build NMD to the Athenian decision in 479 BC to build its "Long Walls" linking Athens and its major seaport.First, the paper defines the three elements of U.S. nuclear deterrence posture: retaliation, defense, and dissuasion. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…These improvement in the function of liver, kidney and antioxidants enzymes could be explain based on the effect of magnetic treatments to improving solubility of minerals of water, which facilities the transfer of the nutrients via improving membrane permeability to animal cells, thus nutrients uptakes and utilization as the water is the media for all biological and metabolic reactions (El-Hanoun, 2014). (Davis and Rawls, 1996;Lynch, 2000) indicated that magnetically treated water activates enzymes and acts as a coenzyme cofactor so that it helps the enzyme to take its shape and increase the efficiency and activation of enzyme sites. The decrease in the activity of the enzymes GOT and GPT in the serum of ewes may be due to the increase in the concentration of total protein in the blood serum in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…These improvement in the function of liver, kidney and antioxidants enzymes could be explain based on the effect of magnetic treatments to improving solubility of minerals of water, which facilities the transfer of the nutrients via improving membrane permeability to animal cells, thus nutrients uptakes and utilization as the water is the media for all biological and metabolic reactions (El-Hanoun, 2014). (Davis and Rawls, 1996;Lynch, 2000) indicated that magnetically treated water activates enzymes and acts as a coenzyme cofactor so that it helps the enzyme to take its shape and increase the efficiency and activation of enzyme sites. The decrease in the activity of the enzymes GOT and GPT in the serum of ewes may be due to the increase in the concentration of total protein in the blood serum in blood serum.…”
Section: Discussionmentioning
confidence: 99%